Postoperative Complications After Distal Pancreatectomy Performed During Cytoreductive Surgery for Gynecologic Malignancies. Issue 6 (July 2015) - Mahdi, Haider; Rose, Peter G.; Gonzalez, Samantha; DeBernardo, Robert; Knight, Jason; Michener, Chad; Moselmi-Kebria, Mehdi
<x xml:space="preserve">Abstract</x> Objectives To investigate the incidence of pancreatic leak and other postoperative complications after distal pancreatectomy performed during debulking surgery for gynecologic malignancies. Methods All patients who underwent distal pancreatectomy during their debulking surgery from 2010 to 2014 were identified. Postoperative complications within 30 days and pancreatic leak within 120 days after surgery were included. Results Eighteen patients met the inclusion criteria. The median age was 62 years (36–78 years). Four patients (22%) were admitted to the intensive care unit, and the average length of hospital stay was 10 days. Nine patients developed postoperative complications within 30 days after surgery (50%) with no perioperative mortality up to 90 days after surgery. No patients required reexploration. The median time from surgery to initiation of chemotherapy was 39.5 days. Two patients developed pancreatic leak (11%). Among the patients who developed pancreatic leak, the average length of hospital stay was 11.5 days and time to initiation of chemotherapy was 75 days. Conservative management was successful in both cases. Conclusion In this series, the rate of pancreatic leak was lower than previously reported with no perioperative mortality or surgical reexploration. However, the time to initiation of chemotherapy was delayed in those who developed pancreatic leak. These data are important in patient counseling and decision making at the time of debulking surgery. Gynecologic oncologists considering distal pancreatectomy should be familiar with perioperative management of these patients.